Assement Efficacy and Complication of the Distance between Phototherapy Lamps and Neonate's Body Level on Serum Bilirubin Decrease and Phototherapy Complications in Neonatal Hyperbilirubinemia - Roghayeh Zardosht; Ahmad Shah Farhat; Reza Saeidi; Fatemeh Parvin (Mashhad University of Medical Sciences, 2019)
Background: Jaundice is one of the most leading causes of neonate hospitalization (51.8%) during the first four weeks of life, and phototherapy is one of the most common and safest methods for the treatment of jaundice. Different results have been obtained from the studies conducted on the investigation of factors affecting increased phototherapy effect on the reduction of neonatal jaundice. However, there still exist many questions concerning the methods that maximize the effect of phototherapy. The current research aimed to determine the effect of the distance between phototherapy lamps and neonate's body on the reduction of serum bilirubin and phototherapy complications in the neonates with physiologic jaundice. Methods: The study was carried out on 60 newborns with jaundice. The neonates in the intervention group were put under phototherapy within a distance of 20 cm, and the ones in the control group underwent phototherapy within a distance of 40 cm. Daily bilirubin was measured at times 0, 12, and 24, and the neonates were examined in terms of serum bilirubin reduction and phototherapy complications. Results: The obtained results revealed that phototherapy within the distance of 20 cm causes more reduction in the total bilirubin 12 and 24 hours after phototherapy. However, there was no significant difference between bilirubin 48 hours after phototherapy and phototherapy duration and the complications between the two groups. Conclusion: Based on the results, the method of phototherapy distance reduction could be used as a safe and effective way for the quicker reduction of serum bilirubin level, prevention of hyperbilirubinemia complications and complications of blood transfusion in neonates with physiologic jaundice.